Upaya Penerapan Konseling REBT Format Kelompok untuk Mengurangi Pikiran Negatif dan Rasa Bersalah pada Korban Kekerasan Seksual - Apriliana, Yona; Karneli, Yeni; N, Netrawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sexual violence is a traumatic experience that leaves long-term psychological impacts on victims, particularly in the form of negative thoughts and deep-seated guilt. Cognitive distortions, such as self-blame, often hinder the recovery process. This article aims to examine the effectiveness of Rational Emotive Behavior Therapy (REBT) in reducing negative thoughts and guilt among survivors of sexual violence. The study employs a literature review method, analyzing various relevant scholarly sources. Findings indicate that REBT is effective in challenging and replacing irrational beliefs with healthier and more logical thinking patterns. This approach helps survivors reconstruct a positive self-identity and alleviate emotional distress. However, its application must be adapted to the cultural context and emotional condition of the victims. The study offers practical implications for counselors in designing empathetic and evidence-based interventions for survivors of sexual violence.